First Impressions Matter. Interview Interactions and Interviewers' Subjective Measures - Karina Doorley; Eva Sierminska (Institute of Labor Economics (IZA), 2023)
This note uses a unique dataset for Germany which contains interviewer-rated physical appearance assessments of survey respondents both before and after the interview to address three questions. Firstly, after the first impression of an individual's physical appearance, what characteristics make people appear more or less attractive to interviewers? We find that these differ widely by respondent gender. Second, how does this second impression vary by interviewer characteristics? We note differences by interview gender, education and age which has implications for the design of surveys which attempt to abstract "objective" measures of respondent characteristics from interviewers. Lastly, is the first impression of physical appearance most important in determining income or is there also a role for the second impression? Here we find that while it is the first impression which matters, the correlation between interviewer-rated attractiveness and income is higher if it is recorded by somebody of the same gender.
Keywords: J31; C83; J70; 330; survey; beauty; income